Battle Formation of the Sumerian Phalanx: the Stele of the Vultures and Textual Evidence - MAEKAWA, Kazuya (Bulletin of the Society for Near Eastern Studies in Japan, 2003)
The battle formation of the Sumerian phalanx, which is carved in relief on the reverse of the Stele of the Vultures, is studied in this article in light of textual sources, i. e., administrative documents, almost contemporary to the Stele, and later royal hymns and lexical texts. DP 135 (dated around 2370 B. C.) suggests that a complete Sumerian phalanx was composed of thirty-two soldiers: a commander, a sub-commander, twenty-four spearmen and six shield-bearers. According to the Stele of the Vultures (produced 50 years or more earlier than DP 135), on the other hand, Lagashite troops of thirty men in phalanx formation, being led by King Eannatum, charged on the enemy. In my view, the phalanx of the Stele is composed of the following soldiers: a sub-commander, a shield-bearer who protects the sub-commander, twenty-four spearmen standing in four lines, and four shield-bearers protecting the first four spearmen of the respective lines. Although neither a commander nor a man holding a protective shield for the commander is found in the Stele, the battle formation drawn on the Stele differs only superficially from what DP 135 suggests. King Eannatum, whom the Stele depicts as standing unguarded in front of his troops in phalanx, plays the role of commander. I reconstruct the phalanx of the Stele as follows. The head and the two feet that are found on the far right (as one faces it) in the phalanx relief of the Stele (called Head 1-Feet 1-2 in this article) represent the sub-commander of the troops. The second soldier, with the head and feet second from the right in relief (Head 2-Feet 3-4), protects the sub-commander with his large shield. The spearman of Head 3-Feet 5-6 stands at the head of the six men in the first line, being guarded by the shield-bearer of Head 4-Feet 7-8, and so on. On the far left of the Stele, the head and feet of the spearman, who is positioned first in the fourth line, are only imperfectly carved (Head 9-Feet 17-18). Two more heads are in relief on the left side board of the Stele, with the carvings of their four feet being completely lost from the board (Head 1′-Feet 1′-2′ Head 2′-Feet 3′-4′). I conclude that the spearman of Head 9-Feet 17-18, found last on the reverse, occurs again on the right of the side board (Head 1′-Feet 1′-2′) and that he is protected by the fifth shield held by the man of Head 2′-Feet 3′-4′ on his left. The term ama-ERIN2 refers to shield-bearers in DP 135. In the other contemporary text (Nik 1 3), however, it occurs as a designation of the whole army (composed of both shield-bearers and spearmen). The expression ama-erin2-na of the later periods, which is often interpreted by Assyriologists to denote “the main body of the troops” on the basis of its Akkadian translation, seems to have been derived from ama-ERIN2 with a meaning as found in Nik 1 3. Like Eannatum of Pre-Sargonic Lagash, King Shulgi of Ur, dated to the first half of the 21st century B. C., was obligated to stand alone before his troops (called ama-erin2-na) [Šulgi B 31; Šulgi E 209]. It is rather doubtful, however, that Shulgi's troops were in phalanx formation as had been the case of the soldiers of Eannatum. ERIN2-suh5-ha, which is used as a designation for spearmen in DP 135, occurs again in a later lexical text in slightly different writing (erin2-suh). ERIN2-suh5-ha is possibly interpreted to mean “selected troops (of spearmen guarded by shield-holders).”